Makna Kata “Kudus” Berdasarkan 1 Petrus 1:15-16 - Udju, Daniel (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
This research aims to explore the meaning of the word "holy" in a Christian context based on the Letter 1 Peter 1:15-16. The concept of holiness has deep theological significance in Christianity, and this text provides an important basis for understanding the concept. This research uses a qualitative approach method, by collecting data through analysis of Bible texts, books, scientific journals and analysis of related documents. Data analysis was carried out thematically to identify patterns and themes in understanding the concept of "holy." The results of this research reveal the complexity of the meaning of the word "holy" in the context of 1 Peter 1:15-16. There are various understandings of this concept, including an understanding of holiness as a call to a different life and an understanding of holiness as a reflection of God's holy nature. The conclusions of this research provide deep insight into how the concept of "holy" can be translated and applied in contemporary Christian life. The implications of this research have strong relevance in the development of Christian spirituality and a deeper understanding of the call to be "holy," as stated in Scripture.   Keywords: Bible, Christian, God, Holy, 1 Peter 1:15-16